Efficacy of combination of oral mifepristone and vaginal misoprostol in termination of pregnancy up to 63 days of gestation - Gupta, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Unsafe and illegal abortions are one of the major problems in women health in India. Despite legal approval for medical termination of pregnancy in 1971, unsafe abortion still remains the third leading cause of maternal deaths in the country, contributes eight percent of such deaths annually. The objective of this study was to study efficacy of Mifepristone 200 mg orally followed 36-48 hours later by Misoprostol 800 microgms per vaginally in women undergoing medical termination of early pregnancy (up to 63 days of gestational age). Methods: The present study included 60 pregnant women requesting termination of pregnancy in the first trimester. Women who fulfilled the inclusion criteria were included in the study. Women without medical or surgical contraindications to Mifepristone and Misoprostol were included. Patients with previous caesarean sections were also included. Results: In our study 60 women were included, majority were in age group 20-29 years of age and majority of cases were primipara or multipara. The success rate in terms of complete abortion was 97%, 2% needed surgical evacuation and 1% lost to follow up. Side effects were nausea, vomiting, diarrhoea, abdominal cramps, pyrexia etc. The method proved to be safe, effective, cheap, non-invasive and has minimal or no complications. Conclusions: Medical termination of pregnancy with oral mifepristone and vaginal misoprostol is an effective method for first trimester abortion. The prerequisite for the method is patient counselling, patient participation and willingness for regular follow up and to report any complication. Hence this method comes out to be a safe alternative to surgical method which is invasive and costly.